A study on a positive approach to control inventory and distribution planning by Rothmans of Pall Mall (Malaysia) Berhad / Azizuddin Ahmad - Azizuddin, Ahmad (Faculty of Business and Management, 1993)
The idea of doing this thesis on inventory control and distribution planning arise when thinking of how much important of these two Physical Distribution mix in today modern materials. The need to have an expertise Distribution managers that can handled responsibility and ability to think of how to control their stock in hand and searching for market competition has come to as a must for every manufacturing companies. I would be very glad if this thesis on the subject mentioned would help Rothmans of Pall Mall (Malaysia) Sdn.Bhd. to improve its inventory control and distribution planning.